Using p-median to solve location design problems - Shnaishel Cheetar*, Alaa (Journal of Economics and Administrative Sciences, 2024)
Purpose: This research mostly concentrates on guiding pupils to their secondary schools following their accomplishment in the early elementary education phase. The primary challenge is the establishment of additional schools to accommodate the significant population growth resulting from expansion in emerging areas. Theoretical framework: Scholarly literature has thoroughly examined the P-Median problem and applied it across various domains, including cluster analysis, quantitative psychology, marketing, the communications sector, sales force design, and political constituency division. Design/methodology/approach: This study aims to propose a customization form based on the P-Median issue, taking into account its properties and structure. The P-Median problem optimizes the allocation of the facility (student school) to the demand point (student home) based on the average distance. This tool determines the best placement for a few schools. Findings: In this research, of the form (P-Median) and the implementation of math results, which the results showed that sites number (4,3,1) in table No. (4) and knowledge in Table No. (1), the places where schools can be created because they are the most sought -after as they are newly constructed. These new schools can also accommodate the increase in the number of students in other regions. Research, Practical & Social implications: It is possible to study and develop the proposed model according to new data and in line with the requirements. Originality/value: The diversity of publishing and studying novel allocation methods increases cognitive capacity, particularly for new, relevant, and helpful issues, because they are practical for distributing the service facilities the country requires. Authors’ individual contribution: Conceptualization — A.S.C.; Methodology — A.S.C.; Formal Analysis — A.S.C.; Investigation — A.S.C.; Data Curation — A.S.C..; Writing —Original Draft — A.S.C.; Writing — Review & Editing — A.S.C.; Visualization — A.S.C.; Supervision — A.S.C.; Project Administration — A.S.C. Declaration of conflicting interests: The Authors declare that there is no conflict of interest. Paper type: Research Paper